Strengthening Succession Planning Strategy at PT Gag Nickel - Ahlan Novia Garnasih; Ratri Wahyuningtyas (Journal Research of Social Science, Economics, and Management, 2025)
Succession planning is vital for leadership continuity, yet PT Gag Nikel, an ANTAM subsidiary, faces challenges in implementing it effectively. Although a human resource system exists, succession planning at PT Gag Nikel remains reactive, unstructured, and insufficiently integrated, threatening operational sustainability. This qualitative research aims to strengthen succession planning strategy at PT Gag Nickel through analyzing current conditions and offering strategic recommendations. Data were collected via in-depth interviews, focus group discussions, observations, and document analysis, using Creswell’s model and NVivo 12. Four key informants were purposively sampled, including the Acting President Director, Director of Finance Risk Management and HR, and Human Capital staff. Key findings reveal critical issues such as the absence of a formal succession system, weak communication, and the lack of development plans linked to performance assessments. Seven strategic positions remain vacant; internal candidates fail to meet qualifications due to educational mismatches, insufficient tenure, assessment center failures, and missing competency certifications. Recommendations include establishing a structured succession system through a three-phase roadmap; developing a talent matrix based on performance and potential; implementing Individual Development Plans (IDPs) for targeted competency growth; conducting leadership training focusing on digital skills, adaptive leadership, and ESG principles; and applying KPI-based evaluations with 360-degree feedback. These strategies are essential to ensure sustainable leadership continuity and organizational resilience. This research contributes to succession planning literature within the mining sector and provides a practical framework for companies facing similar challenges in remote operations, supporting sustainable human resource development and organizational effectiveness.